The protective role of methyl jasmonates (MeJA) in capsicum (Capsicum annuum var. conoide) under drought stress: Growth, photosynthetic, and biochemical responses - SHAH, SAJID ALI; CHIB, SUNNY SINGH; ASLAM, SAIMA (The Indian Journal of Agricultural Sciences, 2026)
Drought stress severely limits crop productivity and negatively affects the growth and physiology of capsicum (Capsicum annuum var. conoide). The present study was carried out during 2023–2024 at the Department of Biotechnology, Baba Ghulam Shah Badshah University, Rajouri, Jammu and Kashmir to evaluate the role of foliar-applied methyl jasmonate (MeJA, 25 and 50 μM) in improving drought tolerance. Drought significantly reduced growth, biomass, yield traits, photosynthetic pigments, and induced oxidative damage (H2O2 and MDA accumulation). MeJA application, particularly at 25 μM, alleviated these effects by enhancing growth, restoring pigment content, boosting antioxidant enzymes (CAT and SOD), improving protein levels, regulating elemental balance (C, Ca, K), and partially recovering stomatal traits. Statistical analysis confirmed the significance of these improvements. Overall, low-dose MeJA foliar spray effectively enhances drought resilience in C. annuum var. conoide under water-deficit conditions.